Posterior Polymorphous Corneal Dystrophy Coexisting with Central Serous Chorioretinopathy – Case Report - Sabal, Barbara (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
Posterior polymorphous corneal dystrophy is a rare, usually bilateral and asymmetric corneal genetic disorder with wide clinical manifestation. Central serous chorioretinopathy is common nonsurgical retinal disorder. Etiology, risk factors, pathomechanism of discussed diseases are not completely clear. We describe a case of unusual coexistence of these disease entities in a middle-aged woman and its potential association.